REDUCING OVERWEIGHT AND OBESITY AMONG ADULT MEN AND WOMEN THROUGH EXERCISE PARTICIPATION - Omonu, J. Boyı (European Scientific Journal, ESJ, 2015)
This paper examines the roles of physical exercise in reducing overweight and obesity among adult men and women who live sedentary life-styles in the society. The paper equally isolated the consequences of lack of physical activity in sedentary lives and advocated among others, the need to engage in physical exercise. The author points out that exercise participation is sine-qua-non for healthy living for adult men and women in sedentary occupations. A number of recommendations were proffered among which was that individuals should ensure that he/she does not give-in to a sedentary life-style that will prone him/her to be overweight or obese . It was also recommended that Government at all levels should provide sporting facilities where adult men and women in the society, particularly those that are already overweight and obese could take part in physical exercise from time to time. This would thus aid them in watching their condition in order to avoid being overweight and to stay healthy.